Благодійна діяльність та фандрайзинг в соціальній роботі: теоретичний аспект - Сидорук, Ірина; Корпач, Надія (Східноєвропейський національний університет імені Лесі Українки, 2019)
Мета дослідження. Благодійність і фандрайзинг тісно пов’язані між собою, оскільки благодійність – це добровільна і безкорислива допомога тим, хто її потребує, а фандрайзинг – один з механізмів, на якому базується реалізація цієї допомоги. Стаття присвячена вивченню особливостей фандрайзингу як засобу ефективного здійснення благодійної діяльності у процесі вирішення соціальних проблем різних категорій населення. Методи дослідження. Представлено аналіз окремих благодійних фондів щодо вирішення нагальних соцальних проблем у сучасному українському суспільстві, обгрунтовано потребу у співпраці фахівців соціальної сфери із благодійними фондами, меценатами, спонсорами. Результат. Доведено, що успішність здійснення фандрайзингу залежить від уміння розробляти проекти, програми, налагоджувати контакти з потенційними партнерами, організаціями і фондами, які можуть профінансувати ці проекти та окреслено перспективні напрями дослідження в середньостроковій перспективі.Charity and fundraising are closely linked. Charity is voluntary and unselfish help to those who need it. Fundraising is one of the mechanisms on which the implementation of this assistance is based. The article is devoted to the study of features of fundraising as a means of effective implementation of charitable activities in the process of solving social problems of different categories of the population. Research methods. The article analyzes the views of modern researchers on the phenomenon of philanthropy in the field of social work. Further consideration was given to the scientific opinion that the spread of philanthropy and its acquisition of form of organized activity caused the emergence of fundraising as a science of planning and streamlining actions that will help organized act both patrons and those who receive charity. Characterized activity of separate foreign and domestic charitable foundations (Victor Pinchuk Foundation, Happy Childhood Foundation, All-Ukrainian Charity «Child Well-being Fund Ukraine», Ukrainian Philanthropic Marketplace, Charitable Fund Klub Dobrodiiv, Charitable Fundation «Lifelover», International Charitable Fund "Caritas Ukraine" and others) on solving urgent social problems in the modern Ukrainian society. The article substantiates the need for cooperation of specialists of the social sphere with charitable foundations, patrons, sponsors. The authors find out the types, forms, stages of fundraising activity. Result. In the article, the authors prove that the success of fundraising depends on the ability to develop projects, programs, to establish contacts with potential partners, organizations and funds that can finance these projects. The perspective directions of research in the medium-term perspective are outlined in the article.
Keywords: благодійна діяльність; charitable activity; фандрайзинг; соціальна робота; фахівці соціальної сфери; фахівці соціальної сфери; благодійні фонди; проект; fundraising; social work; specialists of social sphere; charitable foundations; project